Association between olfactory sensitivity and behavioral responses of Drosophila suzukii to naturally occurring volatile compounds. Issue 3 (19th March 2020) - Corda, Giulia; Solari, Paolo; Dettori, Maria Antonietta; Fabbri, Davide; Delogu, Giovanna; Crnjar, Roberto; Sollai, Giorgia
Abstract: Drosophila suzukii Matsumura (Diptera: Drosophilidae) is an invasive, destructive crop pest that originated in South East Asia. D. suzukii recently invaded Western countries and is threatening both European and American fruit industries. It is extremely attracted to otherwise undamaged, ripening fruits, unlike most other Drosophila species that attack only decaying or rotten fruits. Recent studies on different insect species showed that several naturally occurring compounds of easy market availability showing deterrent action may be used to supplement mass catches with food traps. Based on these considerations, the aim of the present work was to test the effects of some natural compounds (alone or in the mixture) on the olfactory system of the D. suzukii and the behavioral responses evoked. We measured by electroantennogram (EAG) recordings, the olfactory sensitivity of antennae to increasing concentrations of eugenol, vanillin, menthol, cis ‐jasmone; eugenol + vanillin, +menthol, + cis ‐jasmone; vanillin + menthol, + cis ‐jasmone. In addition, the behavioral responses to the same compounds and mixtures were evaluated. Our electrophysiological results show a dose‐response relationship between the EAG amplitudes and the increasing concentrations of the olfactory compound. The behavioral results show that the number of laid eggs is significantly different between the standard diet and the standard diet + natural compound. These results underline a specificity in the olfactory sensitivity and in the ovipositing behavior of D. suzukii females; also, they could be valuable for the identification of key chemicals aimed at the future development of strategies in the management and control of this harmful insect for crops. Highlights: The olfactory system of Drosophila suzukii is responsive to various naturally occurring volatiles in a dose‐response manner. Some of these compounds affect the choice of the oviposition substrate by D. suzukii females. Abstract : The deterrent effect of naturally occurring volatile compounds on the ovipositing females of Drosophila suzukii